Greenhouse gas emissions from Canadian oil sands supply chains to China. (15th July 2022) - Sapkota, Krishna; Gemechu, Eskinder; Oni, Abayomi Olufemi; Ma, Linwei; Kumar, Amit
Abstract: The main purpose of this study is to develop a bottom-up life cycle assessment model to evaluate the greenhouse gas (GHG) emissions associated with the Canadian oil sands supply to China. Two pathways were considered. In pathway I, extracted bitumen is sent to Edmonton for upgrading and pipelined to the Westridge terminal near Vancouver, then shipped to a port in China. In pathway II, extracted bitumen is mixed with diluent, directly pipelined to the Westridge terminal, and shipped to China. The results from both the pipeline and the shipping models suggest that pathway I has better GHG emissions than pathway II on a per-barrel basis. GHG emissions are 2.4–3.5 times lower in pipelining synthetic crude oil (SCO) to Westridge than in pipelining dilbit, without and with a diluent return. The emissions range from 826 − 401 + 701 g CO2 eq/bbl for SCO, 1819 − 719 + 1172 for dilbit without diluent return, and 2684 − 1065 + 1374 g CO2 eq/bbl for dilbit with a diluent return. Shipping SCO has 15% fewer emissions than shipping dilbit. The shipping emissions are due to fuel use in the main engine. The emissions for shipping are 5536 − 914 + 966 g CO2 /bbl for dilbit and 4034 − 822 + 899 g CO2 /bbl for SCO. Highlights: GHG emission performances of Canadian oil sands supply to China were identified. Pipeline GHG emissions range from 826 − 401 + 701 to 1819 − 719 + 1172 g CO2 eq/bbl. Shipping synthetic crude oil has 15% fewer GHG emissions than shipping dilbit. Shipping GHG emissions ranges from 4034 − 822 + 899 to 5536 − 914 + 966 g CO2 /bbl. The synthetic crude oil supply pathway has a higher GHG performance than the dilbit.